Molecular Docking of Natural Alkaloids with Bcl-xL Protein in The Apoptosis Process - Noraziah Nordin; Wan Noraini Wan Sulaiman; Marjanu Hikmah Elias (Universiti Sains Islam Malaysia, 2024)
Malaysian Journal of Science Health & Technology, Volume 10 Issue 2 Page (139–146)